REC SWAG Meeting on Mainstreaming Climate Risk Management Curriculum in Kenya’s Agricultural Extension and Advisory Service - Dinh, Dannie; Hansen, James; Grossi, Amanda; Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to enhance access and use of climate information services (CIS) and validated climate-smart agriculture technologies in Africa, to help these countries strengthen the resilience of their agricultural sectors to the threat posed by climate change. Strengthening the capacity of next users, particularly agricultural extension and advisory service (EAS) providers who work to support farmers in Senegal and five other target countries, is crucial for achieving this goal. AICCRA has worked with national partners to co-develop and transfer curricula, to equip EAS providers to use localized climate information and tools in their work with farmers, to foster agricultural resilience. AICCRA organized a three-day consultative workshop (Nairobi, April 2023) with agricultural EAS providers, and key national institutions (Kenya Meteorological Department (KMD), Kenya Agricultural and Livestock Research Organization (KALRO)) to co-design a short course curriculum on Climate Risk Management in Agricultural Extension (CRMAE) for Kenya’s EAS provider community. In November 2024, the CRMAE curriculum was presented during the Joint Agricultural Sector Consultation and Cooperation Mechanism Sector Working Group on Research, Extension, and Capacity Building (REC-SWAG) at Lake Naivasha Resort, Naivasha, Kenya to validate and endorse the curriculum’s integration in Kenya. This report summarizes the workshop process and outcomes.